A low-cost catalytic electrode for rapid full electrolysis of seawater to produce hydrogen, its preparation and application
By growing nickel sulfide nanosheet arrays in situ on the three-dimensional self-supporting foam surface, an efficient dual-function fully hydrolysis hydroelectric catalyst is formed, which solves the problems of slow kinetics and side reactions of seawater electrolysis in water electrolysis, and achieves a fast, stable and low-cost hydrogen production effect of seawater electrolysis.
Patent Information
- Application Number
- CN202211286421.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-20
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-10-20
AI Technical Summary
The prior art has a slow kinetic problem in water electrolysis, especially in oxygen evolution reactions (OERs). The use of fresh water during large-scale hydrogen production will put pressure on freshwater resources, and seawater electrolysis may lead to side reactions due to the complexity of electrolytes.
A three-dimensional self-supporting foam is used as a catalyst support to grow an array of nickel sulfide nanosheets in situ on its surface to form an efficient dual-function fully hydrolysis electrocatalyst for rapid seawater electrolysis to produce hydrogen.
It realizes a dual-function full-removal aquatic hydrogen that is continuously stable under industrial-grade current density (500mA cm-2), avoids the occurrence of side reactions, improves catalytic performance and stability, and reduces production costs.
Smart Images

Figure CN115505961B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of green hydrogen energy, and in particular relates to a low-cost catalytic electrode for rapid full electrolysis of seawater to produce hydrogen, and its preparation and application. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Hydrogen (H2) is expected to become a renewable and non-polluting energy carrier for storing intermittent solar and wind energy. Water electrolysis is a sustainable and clean route to produce non-polluting hydrogen fuel with high energy density, which is crucial for future renewable energy plans. However, both half reactions of water electrolysis, including hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), suffer from sluggish kinetics. In particular, OER is more challenging due to the strong O=O double bond and multi-step proton / electron transfer process, which greatly hinders the overall efficiency of water electrolysis.
[0004] In addition, most of the current research focuses on freshwater splitting with the addition of electrolytes. Using freshwater as an electrolyte for water electrolysis to produce hydrogen will put heavy pressure on important freshwater resources. Compared with freshwater, seawater accounts for 96.5% of the earth's total water storage and is evenly distributed in space. Therefore, overall seawater splitting to produce H2 is a promising candidate for large-scale H2 production. However, the complexity of electrolytes in seawater may lead to serious side reactions (such as chloride corrosion).
[0005] In addition, the reserves of precious metals on earth are small, while non-precious metals such as nickel, cobalt and iron are not only abundant but also cheap, and can be widely developed and used on a large scale. Recently, electrocatalysts based on non-precious metals have been reported, such as sulfur-doped nickel-iron hydroxide, molybdenum nitride, heterojunction of nickel-molybdenum nitride and nickel-iron nitride, but there are various problems that restrict further application.
[0006] For example, patent CN114196988A discloses a method for preparing a bimetallic sulfide / MXene complex for electrolysis of water and oxygen evolution, which is composed of Ti3C2 MXene and nanosheets, and the nanosheet array is grown in an orderly manner on Ti3C2 MXene. However, the nickel-iron bimetallic sulfide material grown on Ti3C2 MXene is easy to agglomerate, and the preparation method is relatively complicated. At the same time, the nickel-iron bimetallic sulfide material grown on Ti3C2 MXene is a powder sample. Before the electrocatalytic test, the powder sample needs to be mixed with a binder such as Nafion to prepare a slurry. This form of catalyst has the following disadvantages: a) Nafion is used as a binder to cover the surface of the material, which reduces the exposure of the material during the catalytic process and reduces the catalytic performance; b) The powder sample and the substrate are bonded by a binder, which is easy to fall off during the catalytic process, resulting in reduced stability of the material; c) Nafion itself has poor conductivity, and covering the catalyst surface will reduce the mass transfer performance of the material, thereby reducing the catalytic activity. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a low-cost catalytic electrode for rapid full electrolysis of seawater to produce hydrogen, so as to achieve the following results: -2 )Continuous and stable dual-function full water splitting to produce hydrogen.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The first aspect of the present invention provides a low-cost catalytic electrode for rapid full electrolysis of seawater to produce hydrogen, comprising:
[0010] Catalyst carrier;
[0011] A nickel-iron sulfide nanosheet array is in-situ grown on the surface of the catalyst carrier;
[0012] Wherein, the catalyst carrier is a three-dimensional self-supporting foam.
[0013] The present invention designs a highly efficient bifunctional full water splitting electrocatalyst derived from non-precious metals, which has very broad application prospects for rapid seawater electrolysis to produce hydrogen.
[0014] Compared with patent CN114196988A, the material of the present invention is in-situ grown on the surface of the foam substrate and has a very high bonding effect with the substrate, so it can achieve very high stability; 2) the material itself has a nanosheet array structure, and the substrate itself is porous and has a multi-level pore structure, which can accelerate the transmission and diffusion of the electrolyte; 3) the strong bonding between the catalyst and the substrate will also increase the mass transfer rate of the material and improve the catalytic performance; 4) the material preparation is simple, and the prepared material can be directly used for full electrolysis of alkaline seawater.
[0015] The second aspect of the present invention provides a method for preparing a low-cost catalytic electrode for rapid full electrolysis of seawater to produce hydrogen, comprising:
[0016] uniformly mixing nickel salt, iron salt, ammonium fluoride and urea in a solution to obtain a mixed solution;
[0017] placing a three-dimensional self-supporting foam in the mixed solution and heating it for reaction to obtain a nickel-iron double metal hydroxide precursor electrode;
[0018] The nickel-iron double metal hydroxide precursor electrode is mixed with a sulfur salt in a solution to fully immerse it, and heated to react. After the reaction is completed, the electrode is washed to obtain a nickel-iron sulfide electrode.
[0019] The third aspect of the present invention provides the use of the above-mentioned catalytic electrode in catalyzing hydrogen evolution at the cathode and oxygen evolution at the anode, and the catalytic reactions include: oxygen evolution reaction, hydrogen evolution reaction and full hydrolysis reaction of fresh water, alkaline simulated seawater and alkaline seawater.
[0020] Beneficial effects of the present invention
[0021] (1) The electrode of the present invention serves as a dual-function seawater electrolysis hydrogen production electrode with hydrogen evolution at the cathode and oxygen evolution at the anode, thus avoiding the pollution and waste of using different catalysts.
[0022] (2) The three-dimensional nanosheet array structure of the electrode of the present invention helps to expose more active sites and improve the proton and gas mass transfer rates. The synergistic effect of the bimetallic compounds improves the intrinsic catalytic activity of the electrode. The sulfur anions oxidized on the surface during the catalytic process can inhibit the adsorption of chloride ions on the surface. Based on a variety of excellent structural properties, it can demonstrate an outstanding dual-functional seawater rapid full electrolysis hydrogen production.
[0023] (3) The edible precursors for preparing the electrodes of the present invention are inexpensive, abundant in reserves, and easy to mass produce and apply in future industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0025] Figure 1 It is a schematic diagram of the synthesis route for preparing the nickel-iron sulfide nanosheet array of the present invention.
[0026] Figure 2 These are field emission scanning electron micrographs (a, b) of the nickel-iron sulfide nanosheet arrays prepared in Example 1 of the present invention.
[0027] Figure 3Element distribution diagrams (a, b, c, d) of the nickel iron sulfide nanosheet array prepared in Example 1 of the present invention.
[0028] Figure 4 This is an X-ray diffraction pattern of the nickel-iron sulfide nanosheet array prepared in Example 1 of the present invention.
[0029] Figure 5 This is a spherical aberration electron microscope image of the nickel-iron sulfide nanosheet array prepared in Example 1 of the present invention.
[0030] Figure 6 This is a field emission scanning electron microscope image of the nickel iron sulfide nanosheet array prepared in Comparative Example 1 of the present invention.
[0031] Figure 7 It is an X-ray diffraction pattern of the nickel-iron sulfide nanosheet array prepared in Comparative Example 1 of the present invention.
[0032] Figure 8 These are the electrochemical test results of the nickel iron sulfide nanosheet array and the precursor nanosheet array prepared in Example 1 of the present invention and Comparative Example 1, wherein (a) is the linear sweep voltammetry curve of the oxygen evolution reaction in 1M KOH electrolyte; and (b) is the Tafel curve of oxygen evolution in 1M KOH electrolyte.
[0033] Fig. 9 It is the linear sweep voltammetric curve of the oxygen evolution reaction of the nickel iron sulfide nanosheet array prepared in Example 1 of the present invention in 1M KOH, 1M KOH+0.5M NaCl (simulated seawater) and 1M KOH+seawater (alkaline seawater).
[0034] Fig.10 This is a stability curve of the change in current density over time of the oxygen evolution reaction of the nickel-iron sulfide nanosheet array prepared in Example 1 of the present invention in alkaline seawater.
[0035] Fig.11 These are the electrochemical test results of the nickel iron sulfide nanosheet array and the precursor nanosheet array prepared in Example 1 of the present invention and Comparative Example 1, wherein (a) is the linear sweep voltammetry curve of the hydrogen evolution reaction in 1M KOH electrolyte; and (b) is the Tafel curve of hydrogen evolution in 1M KOH electrolyte.
[0036] Fig.12 It is a linear sweep voltammetric curve of hydrogen evolution reaction of the nickel-iron sulfide nanosheet array prepared in Example 1 of the present invention in 1M KOH, simulated seawater and alkaline seawater.
[0037] Fig.13 This is a stability curve of the change in current density over time of the hydrogen evolution reaction of the nickel-iron sulfide nanosheet array prepared in Example 1 of the present invention in alkaline seawater.
[0038] Fig.14 These are the electrochemical test results of complete water splitting assembled with the nickel-iron sulfide nanosheet array and the precursor nanosheet array prepared in Example 1 of the present invention and Comparative Example 1 as the anode oxygen evolution reaction and the cathode hydrogen evolution reaction, respectively, wherein (a) is the linear sweep voltammetry curve of the complete water splitting in 1M KOH electrolyte; (b) is the linear sweep voltammetry curve of the complete water splitting in alkaline seawater.
[0039] Fig.15 This is a stability curve of the change in current density over time of the complete water splitting reaction of the nickel-iron sulfide nanosheet array prepared in Example 1 of the present invention in alkaline seawater. DETAILED DESCRIPTION
[0040] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0041] A low-cost catalytic electrode for rapid full electrolysis of seawater to produce hydrogen. The catalytic electrode uses a three-dimensional self-supporting foam as a catalyst carrier, and an array of nickel-iron sulfide nanosheets is in situ grown on the surface of the carrier as a catalyst.
[0042] In some embodiments, the three-dimensional self-supporting foam includes: nickel foam, copper foam, nickel-iron foam, titanium foam, and carbon cloth.
[0043] In some embodiments, the catalytic electrode is a bifunctional electrode for cathode hydrogen evolution and anode oxygen evolution.
[0044] A low-cost catalytic electrode for rapid full electrolysis of seawater to produce hydrogen comprises the following preparation steps:
[0045] Step 1, dissolving nickel salt, iron salt, ammonium fluoride and urea weighed according to a stoichiometric ratio in a certain amount of deionized water to form a solution;
[0046] Step 2, placing the three-dimensional self-supporting foam in the solution of step 1, reacting in a reaction vessel at a specific temperature and pressure for a certain period of time, to obtain a nickel-iron double metal hydroxide precursor electrode containing a specific metal ratio;
[0047] Step 3, mixing the nickel-iron double hydroxide precursor electrode obtained in step 2 with a certain amount of sulfur salt in deionized water, allowing it to be fully immersed, reacting in a reaction vessel at a specific temperature and pressure for a certain period of time, and after the reaction is completed, rinsing with deionized water to obtain a nickel-iron sulfide electrode.
[0048] In some embodiments, nickel salt and iron salt are selected from any soluble metal salt, the molar ratio of nickel salt: iron salt is 1:10-10:1, the total molar concentration of metal salt is 10-100 mM, the molar ratio of ammonium fluoride to total metal salt is 5:1-1:5, the molar ratio of urea to total metal salt is 1:1-10:1, and ammonium fluoride and urea do not affect each other.
[0049] In some embodiments, the reaction temperature of step 2 is 90-200° C., the reaction time is 2-72 hours, and the container is a closed container.
[0050] In some embodiments, the sulfur source used in step 3 can be: sodium sulfide, thioacetamide, thiourea and sulfur powder, the molar concentration of the sulfur source is 0.1-1M, the reaction temperature is 80-200°C, the reaction time is 2-72h, and the container is a closed container.
[0051] The present invention provides a low-cost catalytic electrode for rapid full electrolysis of seawater to produce hydrogen. The catalytic reaction includes oxygen evolution reaction, hydrogen evolution reaction and full hydrolysis reaction of fresh water, alkaline simulated seawater and alkaline seawater.
[0052] Combination Figure 1 The present invention prepares the anode catalytic electrode according to the following steps:
[0053] Step 1: Weigh 10-100 mM nickel salt, 10-100 mM iron salt, 20-200 mM ammonium fluoride and 50-500 mM urea, add them into a certain amount of deionized water, and stir evenly to form a mixed solution;
[0054] Step 2: placing the three-dimensional self-supporting foam in the solution prepared in step 1, reacting in a closed container at 90-200° C. for 2-72 hours to obtain a nickel-iron double hydroxide precursor electrode containing a specific metal ratio;
[0055] Step 3: Mix the nickel-iron double hydroxide precursor electrode obtained in step 2 with 0.1-1M sulfur source in deionized water, fully immerse it, and react in a sealed container at 80-200° C. for 2-72 hours. After completion, rinse with deionized water to obtain a nickel-iron sulfide electrode.
[0056] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0057] Example 1
[0058] Step 1: Weigh 50 mM nickel nitrate, 50 mM ferric nitrate, 100 mM ammonium fluoride and 250 mM urea into 40 mL of deionized water and stir to form a mixed solution;
[0059] Step 2: 2*3cm 2 The nickel foam is placed in the solution prepared in step 1, and reacted in a closed container at 120° C. for 6 hours to obtain a nickel-iron double hydroxide precursor electrode (NiFe-LDH / NF) with a Ni:Fe ratio of 1:1;
[0060] Step 3: Add the NiFe-LDH / NF electrode obtained in step 2 to 40 mL of an aqueous solution containing 0.2 M sodium sulfide, and react in a sealed container at 100° C. for 8 h; after completion, rinse with deionized water to obtain a nickel iron sulfide electrode (NiFeS / NF).
[0061] The field emission scanning electron microscopy image of the obtained NiFeS / NF electrode is shown in Figure 2 As shown, it shows that the NiFeS / NF electrode is an ordered array of nanosheets uniformly grown on the NF surface. The relatively thin thickness of the nanosheets can expose more catalytic active sites. The open pores between the nanosheets and the intrinsic porosity of the NF substrate are conducive to the diffusion of the electrolyte, the desorption and transfer of gas products. At the same time, the nanosheet array deposited in situ on the NF surface has strong adhesion and is not easy to fall off. Not using a binder avoids the active sites from being covered and increases the rapid transfer of protons and electrons. The element distribution of the NiFeS / NF electrode is shown in Figure 1. Figure 3 As shown, it shows that Ni, Fe and S elements are evenly distributed on the nanorods, and Ni and Fe can produce a bimetallic synergistic effect to improve the intrinsic catalytic activity. Figure 4 As shown in Figure 2, the strongest triplet peak is the diffraction peak of the NF substrate, and the other weak peaks are the diffraction peaks of FeNiS, indicating that it has good crystallinity. Further comparison with the PDF card proves its (Ni,Fe)3S4 single-phase structure. The spherical aberration electron microscope image of the NiFeS / NF electrode is shown in Figure 2. Figure 5 As shown, it has good crystallinity, and the distance between adjacent crystal planes is 0.28nm, corresponding to the (311) crystal plane. In summary, the NiFeS / NF electrode was successfully synthesized.
[0062] The linear sweep voltammetric curve of oxygen evolution in 1M KOH electrolyte is as follows Figure 8 As shown in a, at 100 and 500 mA cm -2 The overpotentials of RuO2 and RuO2 are 215mV and 272mV, respectively, which are 115mV and 228mV lower than those of commercial RuO2. The Tafel curve of oxygen evolution in 1M KOH electrolyte is shown in Figure 8 As shown in (b), the Tafel slope of NiFeS / NF is only 56.37 mV dec -1 , much lower than commercial RuO2 (138.33mV dec -1 ), indicating that NiFeS / NF has excellent oxygen evolution kinetics.
[0063] Comparison of linear sweep voltammetry curves of oxygen evolution reaction in 1M KOH, 1M KOH + 0.5M NaCl (simulated seawater) and 1M KOH + seawater (alkaline seawater) Fig. 9 As shown, in alkaline seawater, 500 mA cm -2 The overpotential of 1M KOH is only 300 mV, which is only 12 and 28 mV higher than that of 1M KOH and simulated seawater, respectively. -2 The overpotential at this time is less than the starting potential of the chlorine evolution reaction, which avoids the occurrence of the chlorine evolution side reaction. Therefore, NiFeS / NF has excellent seawater electrolysis oxygen performance. The stability curve of the current density of the oxygen evolution reaction in alkaline seawater over time is shown in Figure 2. Fig.10 As shown, at 100 and 500 mA cm -2 After running for 24 hours, it still remained stable and the performance did not decay, indicating that the NiFeS / NF electrode has good stability for oxygen evolution in alkaline seawater electrolysis. In summary, the NiFeS / NF electrode can be used as an anode oxygen evolution catalytic electrode for rapid seawater electrolysis to produce hydrogen.
[0064] The linear sweep voltammetric curve of hydrogen evolution in 1M KOH electrolyte is as follows Fig.11 As shown in a, at 100 and 500 mA cm -2 The overpotentials are 196mV and 292mV respectively. The Tafel curve of hydrogen evolution in 1M KOH electrolyte is shown in Fig.11 As shown in (b), the Tafel slope of NiFeS / NF is only 102.93 mV dec -1 , much lower than the NF substrate (204.11mV dec -1 ), indicating that NiFeS / NF has excellent hydrogen evolution kinetics.
[0065] Comparison of linear sweep voltammetry curves of hydrogen evolution reaction in 1M KOH, 1M KOH + 0.5M NaCl (simulated seawater) and 1M KOH + seawater (alkaline seawater) Fig.12 As shown, in alkaline seawater, 500 mA cm -2 The overpotential is only 347 mV, which is only 55 and 60 mV higher than 1 M KOH and simulated seawater, respectively. Therefore, NiFeS / NF has excellent seawater electrolysis hydrogen performance. Especially in alkaline seawater at 500 mA cm -2 After continuous hydrogen evolution for 24 hours, it remains stable ( Fig.13 ), there is no obvious voltage increase, indicating that the NiFeS / NF electrode also has good stability in hydrogen evolution in alkaline seawater electrolysis. In summary, the NiFeS / NF electrode can be used as a cathode hydrogen evolution catalytic electrode for rapid seawater electrolysis to produce hydrogen.
[0066] The linear sweep voltammetry curve of water decomposition in 1M KOH electrolyte is as follows Fig.14 As shown in a, NiFeS / NF is used as cathode and anode respectively, and only 1.65V is required to achieve 100mA cm -2 In alkaline seawater, only 1.67V is required to reach 100mA cm -2 The current density ( Fig.14 b), indicating that NiFeS / NF can resist the interference of other ions in seawater and has excellent performance in the complete decomposition of seawater. The stability curve of the current density of the complete decomposition of seawater in alkaline seawater over time is shown in Fig.15 As shown, at 100 and 500 mA cm -2 After running for 25 hours, it still remained stable and the performance did not decay, indicating that the NiFeS / NF electrode has good stability in alkaline seawater splitting. In summary, the NiFeS / NF electrode can be used as a bifunctional catalytic electrode for rapid seawater electrolysis to produce hydrogen.
[0067] Example 2
[0068] Step 1: Weigh 50 mM nickel nitrate, 50 mM ferric nitrate, 100 mM ammonium fluoride and 250 mM urea into 40 mL of deionized water and stir to form a mixed solution;
[0069] Step 2: 2*3cm 2 The carbon is arranged in the solution prepared in step 1, and reacted in a closed container at 120° C. for 6 hours to obtain a nickel-iron double hydroxide precursor electrode (NiFe-LDH / NF) with a Ni:Fe ratio of 1:1;
[0070] Step 3: Add the NiFe-LDH / NF electrode obtained in step 2 to 40 mL of an aqueous solution containing 0.2 M sodium sulfide, and react in a sealed container at 100° C. for 8 h; after completion, rinse with deionized water to obtain a nickel iron sulfide electrode (NiFeS / NF).
[0071] Example 3
[0072] Step 1: Weigh 25 mM nickel nitrate, 75 mM iron nitrate, 100 mM ammonium fluoride and 250 mM urea into 40 mL of deionized water and stir to form a mixed solution;
[0073] Step 2: 2*3cm 2 The nickel foam is placed in the solution prepared in step 1, and reacted in a closed container at 120° C. for 6 hours to obtain a nickel-iron double hydroxide precursor electrode (NiFe-LDH / NF) with a Ni:Fe ratio of 1:3;
[0074] Step 3: Add the NiFe-LDH / NF electrode obtained in step 2 to 40 mL of an aqueous solution containing 0.2 M sodium sulfide, and react in a sealed container at 100° C. for 8 h; after completion, rinse with deionized water to obtain a nickel iron sulfide electrode (NiFeS / NF).
[0075] Example 4
[0076] Step 1: Weigh 50 mM nickel nitrate, 50 mM iron nitrate, 200 mM ammonium fluoride and 250 mM urea, add them into 40 mL deionized water, and stir to form a mixed solution;
[0077] Step 2: 2*3cm 2 The nickel foam is placed in the solution prepared in step 1, and reacted in a closed container at 120° C. for 6 hours to obtain a nickel-iron double hydroxide precursor electrode (NiFe-LDH / NF) with a Ni:Fe ratio of 1:1;
[0078] Step 3: Add the NiFe-LDH / NF electrode obtained in step 2 to 40 mL of an aqueous solution containing 0.2 M sodium sulfide, and react in a sealed container at 100° C. for 8 h; after completion, rinse with deionized water to obtain a nickel iron sulfide electrode (NiFeS / NF).
[0079] Example 5
[0080] Step 1: Weigh 50 mM nickel nitrate, 50 mM ferric nitrate, 100 mM ammonium fluoride and 250 mM urea into 40 mL of deionized water and stir to form a mixed solution;
[0081] Step 2: 2*3cm 2 The nickel foam is placed in the solution prepared in step 1, and reacted in a closed container at 150° C. for 6 hours to obtain a nickel-iron double hydroxide precursor electrode (NiFe-LDH / NF) with a Ni:Fe ratio of 1:1;
[0082] Step 3: Add the NiFe-LDH / NF electrode obtained in step 2 to 40 mL of an aqueous solution containing 0.2 M sodium sulfide, and react in a sealed container at 100° C. for 8 h; after completion, rinse with deionized water to obtain a nickel iron sulfide electrode (NiFeS / NF).
[0083] Comparative Example 1
[0084] Step 1: Weigh 50 mM nickel nitrate, 50 mM ferric nitrate, 100 mM ammonium fluoride and 250 mM urea into 40 mL of deionized water and stir to form a mixed solution;
[0085] Step 2: 2*3cm 2The nickel foam is placed in the solution prepared in step 1 and reacted in a closed container at 150° C. for 6 hours. After the reaction, it is rinsed with deionized water to obtain a nickel-iron double hydroxide electrode (NiFe-LDH / NF) with a Ni:Fe ratio of 1:1.
[0086] The field emission scanning electron microscopy image of the obtained NiFe-LDH / NF electrode is shown in Figure 6 As shown in Figure 2, it shows that the NiFe-LDH / NF electrode is an ordered array of nanosheets uniformly grown on the NF surface. Figure 7 As shown, the strongest triplet peak is the diffraction peak of the NF substrate, and the other weak peaks are the diffraction peaks of NiFe-LDH / NF, which corresponds to the JCPDS No.40-0215 card, indicating its good crystallinity and single-phase crystal structure.
[0087] The linear sweep voltammetric curve of oxygen evolution in 1M KOH electrolyte is as follows Figure 8 As shown in a, at 100 and 500 mA cm -2 The overpotentials of RuO2 and RuO2 are 280mV and 400mV, respectively, which are 50mV and 100mV lower than those of commercial RuO2. The Tafel curve of oxygen evolution in 1M KOH electrolyte is shown in Figure 8 As shown in (b), the Tafel slope of NiFe-LDH / NF is only 80.47 mV dec. -1 , much lower than commercial RuO2 (138.33mV dec -1 ), indicating that NiFe-LDH / NF has good oxygen evolution kinetics.
[0088] The linear sweep voltammetric curve of hydrogen evolution in 1M KOH electrolyte is as follows Fig.11 As shown in a, at 100 and 500 mA cm -2 The overpotentials are 319 mV and 505 mV respectively. The Tafel curve of hydrogen evolution in 1M KOH electrolyte is shown in Fig.11 As shown in (b), the Tafel slope of NiFeS / NF is 186.26 mV dec -1 , much lower than the NF substrate (204.11mV dec -1 ), indicating that NiFe-LDH / NF has excellent hydrogen evolution kinetics. The linear sweep voltammetric curve of water decomposition in 1M KOH electrolyte is shown in Fig.14 As shown in a, NiFe-LDH / NF is used as cathode and anode respectively, and 1.84V is required to reach 100mA cm -2 In alkaline seawater, only 1.86V is required to reach 100mA cm -2 The current density ( Fig.14b), indicating that NiFe-LDH / NF has good performance in fully dissolving seawater.
[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Application of a catalytic electrode in catalyzing hydrogen evolution at a cathode and oxygen evolution at an anode, characterized in that: Catalytic reactions include: Oxygen evolution reaction, hydrogen evolution reaction and perhydrolysis reaction of fresh water, alkaline simulated seawater and alkaline seawater; The method for preparing the catalytic electrode comprises: Step 1: Weigh 50 mM nickel nitrate, 50 mM ferric nitrate, 100 mM ammonium fluoride and 250 mM urea into 40 mL of deionized water and stir to form a mixed solution; Step 2: 2*3cm 2 The nickel foam is placed in the solution prepared in step 1, and reacted in a closed container at 120° C. for 6 hours to obtain a nickel-iron double hydroxide precursor electrode (NiFe-LDH / NF) with a Ni:Fe ratio of 1:1; Step 3: Add the NiFe-LDH / NF electrode obtained in step 2 to 40 mL of an aqueous solution containing 0.2 M sodium sulfide, and react in a sealed container at 100° C. for 8 h; after completion, rinse with deionized water to obtain a nickel iron sulfide electrode (NiFeS / NF); The NiFeS / NF electrode is an ordered array of nanosheets uniformly grown on the NF surface; Ni, Fe and S elements are evenly distributed on the nanorods, and Ni and Fe can produce a bimetallic synergistic effect.
Citation Information
Patent Citations
Ferronickel hydrotalcite-like / ferronickel sulfide heterostructure seawater oxidation electrocatalyst and preparation method thereof
CN114657591A
Cited By
Catalyst for producing hydrogen by electrolyzing seawater under fluctuating working condition and preparation method of catalyst
CN120556070A